Diagnostic damage symptoms and distribution of avocado stem borer (Zeuzera spp.) in the Western Ghats region of India - RANI, A T; MADHU, G S; MURALIDHARA, B M; DEEPAK, G NAYAN; RAJENDIRAN, S; RAKSHITH, V (The Indian Journal of Agricultural Sciences, 2025)
Avocado (Persea americana Mill.), a high-value exotic fruit, is gaining popularity in India due to its nutritional, pharmaceutical, and industrial applications. Initially cultivated as a homestead or intercrop within coffee estates, its large-scale cultivation has recently expanded, leading to shifts in pest dynamics, the documentation of new pests and changes in host ranges commonly observed in horticultural crops. The present study was carried out during 2022–23 at the Central Horticultural Experiment Station (CHES), Chettalli, Kodagu, Karnataka to document the occurrence and distribution of the avocado stem borer, and to identify the pest species using molecular techniques along with detailed observations of damage symptoms. Morphological observations classified the pest under the genus Zeuzera. Molecular analysis of partial COI sequences of avocado stem borer isolates revealed a monophyletic clade with aeglospila, Z. caudata, Z. indica, and Zeuzera spp. (BOLD: AAY7619), but did not cluster with P. coffeae, a common pest of coffee and forest trees, suggesting a different species infesting avocado other than P. coffeae. Surveys revealed stem borer incidence rates of 1.13 ± 0.46% in Kodagu (Karnataka), 8.16 ± 3.11% in Nilgiris and Dindugal (Tamil Nadu), and 12.46 ± 3.58% in Wayanad (Kerala), highlighting the distribution of Zeuzera spp. across South India. This is the first study to document the diagnostics damage symptoms and regional distribution of avocado stem borer, Zeuzera spp., in India. Ongoing research focuses on the species identification through morphological characterization and damage monitoring, to develop effective management strategies as avocado cultivation continues to expand in the Western Ghats.